Evaluating the influence of organizational capability on fundraising success in lebanese non-governmental organizations - Nada Jabbour Al Maalouf; Chadia Sawaya; Jean Elia (Heliyon)
Purpose: Given the significant rise in the number of non-governmental organizations (NGOs worldwide, especially in developing nations, this study investigates the factors influencing fundraising levels among NGOs in Lebanon, a region grappling with profound economic and political challenges. Methodology: Using a quantitative approach, the study analyzes key predictors, including donor funding conditions, financial management practices, organizational fundraising capacity, and competition for funds. Drawing upon a positivist research philosophy and a deductive approach, this study employed a questionnaire distributed via Google Forms. The responses were collected from 124 key decision-makers in NGOs across Lebanon. Statistical analysis using SPSS was employed to investigate the relationships between the variables. Findings: The findings reveal that competition for funds is a significant determinant of fundraising success, underscoring the intense rivalry among NGOs for limited donor resources. In contrast, financial management practices, organizational capacity, and donor funding conditions exhibit negligible impacts, highlighting a crucial divergence from established literature. Contribution and originality: This study addresses a critical gap by examining Lebanon's unique context, where external factors significantly influence fundraising dynamics for NGOs. By offering actionable insights for both NGOs and policymakers, the research advocates for tailored strategies that specifically address local challenges. The findings aim to enhance the sustainability and effectiveness of NGOs within Lebanon's complex landscape. Furthermore, this research contributes to the theoretical discourse on NGO fundraising, emphasizing the necessity for context-specific approaches in developing regions.